The role of type 2 Diabetes mellitus as a risk factor for Alzheimer's and Parkinson's diseases (Research, Society and Development, 2021)
Currently, one of the most significant health problems is the increased incidence of obesity and type 2 Diabetes mellitus (DM2). The most recent epidemiological and clinical research studies have indicated that low physical activity, as well as many genetic and environmental factors are the main causes of these metabolic disorders. It is widely recognized that insulin resistance plays a key role in the development of DM2, disrupting not only the functioning of peripheral tissues, but also the brain. Insulin plays a critical role in the central nervous system participating in neuronal survival, neuroplasticity, memory and cognitive functions. In addition, peripheral insulin resistance results in loss of brain function, which indicates a strong relationship between metabolic disorders, cognitive impairment and the emergence of neurodegenerative diseases. There are links between these different pathologies, such as increased oxidative stress, neuroinflammation, changes in glucose metabolism as well as insulin resistance. Advances in the knowledge of these links may contribute to the development of treatments for the prevention of these pathological events. Based on the above, this study aimed to review the mechanisms associated with DM2 in the development of neurodegenerative diseases, such as Alzheimer’s and Parkinson’s diseases.